Metabolity wtórne w Pinguicula vulgaris L. z kultur in vitro - Ratajczak Lidia
A subject of the experimental research of the thesis was a carnivorous plant -Pinguicula vulgaris L. ssp. vulgaris ? common typical butterwort, from the familyLentibulariaceae ? the Bladderwort family.The species is under protection by law.In the theoretical part of the thesis, general information about carnivorous plants weregiven. 10 botanical families were characterized, concerning genera and plant species.Geographical stands of these taxa were also taken into consideration. Information aboutsecondary metabolites of plants from natural sources and obtained by in vitro culture werecollected from the available literature.The further part of the thesis was devoted to characterization of the family Lentibulariaceaeand Pinguicula species occurrence in Polish flora. Especially precisely, species commontypical butterwort, was described, concerning its morphological structure and biology,chemical constituents found and its medical properties and application.There are two basic subjects - Pinguicula vulgaris L. ssp. vulgaris in vitro cultures andphytochemical investigation, i.e. isolation of secondary metabolites and their chemicalstructure elucidation, in the experimental part of the thesis. Collecting a suitable mass of aplant raw material, species under protection, was only possible by in vitro culture method.The plant material was propagated by direct organogenesis, using modified Murashige-Skoogmedium. After basic methanol extract fractioning, secondary metabolites were isolated fromthe water fraction. To reach this aim, column chromatography and preparative thin layerchromatography were applied, using different adsorbents and suitable mobile phasesselection.Chemical compounds identification was carried out by spectral methods (UV, 1H NMR, 13CNMR, 1H1H-COSY, HMBC, HSQC, NOESY, TOCSY, 2D J) in comparison with literatureinformation. 14 compounds (secondary metabolites), belonging to three chemical classes,were identified: 4 iridoids ? globularin, globularicisin, cinnamoyl ? asistasioside E (trans- andcis-); 4-phenethyl glucosides ? acteoside (trans- and cis-), leucosceptoside A (trans- and cis-);6 flavonoids ? isoscutellarein 8-O-glucuronide, luteolin 7-O-neohesperidoside, hypolaetin 7-215O-neohesperidoside and probably isoscutellarein 8-O-(3?-O-acetyl)glucoside, isoscutellarein8-O-glucuronide methyl ester and hypolaetin 8-O-glucuronide butyl ester.The dominating compound was phenylethanoid ? acteoside.Chromatographical analyses of the plant organs, from in vitro cultures, allowed to determinethe distribution of particular compound groups.Under the permission of The Institute of Nature Conservation of the Polish Academyof Sciences, leaves of the species from natural habitat were collected, and comparativeanalyses were carried out by two dimensional thin layer chromatography (2D TLC) and highperformance liquid chromatography (HPLC).It is worth to emphasize that common typical butterwort has not been reproduced in invitro cultures and the raw material obtained this way has not been analysed phytochemicallyso far.Described Pinguicula vulgaris L. ssp. vulgaris clonal propagation method is a form ofpreserving this rare and protected species.It has been found that free cinnamic acid, which attribute to medicinal properties of P.vulgaris, originated as a result of hydrolysis of cinnamoyl ? asistasioside E.
Keywords: rośliny - chemia; okrytozalążkowe; okrytozalążkowe - metabolizm; okrytozalążkowe - morfologia; okrytozalążkowe - chemia; biotechnologia - metody; substancje organiczne - izolowanie i oczyszczanie; plants - chemistry; angiosperms; angiosperms - metabolism; angiosperms - anatomy & histology; angiosperms - chemistry; biotechnology - methods; organic chemicals - isolation and purification